Legal Review of the Crime of Embezzlement at the North Sumatra Regional Police - Muliadi (International Journal For Advanced Research, 2025)
Embezzlement is a crime against property regulated in the Criminal Code (KUHP), specifically Articles 372 to 377. This crime frequently occurs across various levels of society and generally stems from a relationship of trust that is then abused. In this study, the author examines the legal and normative application of the law to the crime of embezzlement, using case study Report No. 2128/XII/2021/SPKT/North Sumatra Regional Police. The research was conducted through a literature review of laws and regulations, scientific literature, and interviews with investigators from the North Sumatra Regional Police as primary data. The results indicate that the application of the law to the crime of embezzlement has been guided by the Criminal Code and the Criminal Procedure Code, particularly during the investigation and inquiry stages. However, in practice, obstacles remain, such as limited evidence and external factors that can affect the effectiveness of law enforcement. This study emphasizes the need to strengthen the capacity of law enforcement officers and adjust the nominal value of Article 373 of the Criminal Code to make it relevant to current economic conditions.